Arquivologia e arqueologia: teorias e práticas em ambientes de guarda permanente - Godoi, Gleidson Lavoura (2024)
This research is linked to the Postgraduate Program in Cultural Heritage (PPGPC) at the Federal University of Santa Maria (UFSM), in the area of concentration in History and Cultural Heritage and line of research in Archival Documentary Heritage, addressing the topic of management and conservation of documents and materials produced/received in archaeological work. With the intention of demonstrating that different areas can be complementary, this research was based on the principle that Archiveology and Archeology, apparently different, can work with research and treatment sources in opposite ways, but with a concern for the conservation function included in their activities. . Therefore, the dialogue that may exist between the areas of Archiveology and Archeology leads to applicability actions with the possibility of compiling theoretical information from the two sciences, comparing and directing their methods of benefit regarding the conservation of their material assets. The methodological application of the techniques was fundamental to elucidate management and conservation activities. Given the relevance of caring for the materiality of archaeological assets belonging to these custody institutions, this research focused on the use of techniques and methods in materials and documents produced in field activities in Archeology. The central question is “How do institutions handle the management and conservation of their archival and archaeological materials?”The general objective was to analyze document and archaeological management methods and practices, with an emphasis on conservation in permanent storage environments. As a product, an instructive and illustrative manual was created in order to contribute to laboratory activities, providing an overview of how Archeology professionals and students, or even students in related areas, who are interested in this science, should deal with curation procedures. This manual presents the artifacts and the ideal ways of treating them and documents, so that conservation and storage can be carried out well. Science can become similar at some point, it is concluded that this study was versatile, contributing to the training of new researchers who are committed to treating these materials and keeping them well preserved. Through methodological approaches and the interdisciplinarity of knowledge, it was possible to integrate concepts and theories, obtaining a systemic understanding, making the recognition of document management and conservation activities by archivists favorable, making it possible to adapt the same criteria in Archeology.